A two-degree-of-freedom tuned mass damper for offshore wind turbines on floating spar supports. (May 2022) - Laface, Valentina; Alotta, Gioacchino; Failla, Giuseppe; Ruzzo, Carlo; Arena, Felice
Abstract: This paper presents an original approach to mitigate the motion of floating spar supports for offshore wind turbines. A two-degree-of-freedom tuned mass damper device, consisting of a chain of masses, linearly-elastic springs and viscous dashpots, is connected to the system within the nacelle. Considering a four-degree-of-freedom model of the system under simplified aerodynamic rotor loads, as well as Morison hydrodynamic loads, the proposed approach involves tuning the two natural frequencies of the device to the pitch natural frequency of the system and a relevant frequency within the range of the wave loads. Extensive numerical simulations on the OC3-Hywind spar floating wind turbine, for different load cases, prove that the proposed two-degree-of-freedom tuned mass damper is more effective than a standard single-degree-of-freedom one, assuming the two devices feature the same total mass. Further, design parameters are identified for representative loading conditions, in terms of ratio between the two masses within the device and ratio between the total masses of device and system. Highlights: Mitigation of rigid-body oscillations in spar floating wind turbines. Novel 2DOF TMD located in the nacelle of the wind turbine. Numerical simulations on OC3-Hywind spar under turbulent wind and irregular waves. Novel 2DOF TMD proves more efficient than 1DOF TMD with same mass.